The International Confrontation of the Crime of Rape During Armed Conflicts - Ahmed, Syran Taha (Journal of Legal and Political Studies, 2016)
War rape occurring during armed conflicts is rape or other forms of sexual violence committed by combatants during armed conflicts or war or military occupation, as a phenomenon has broader sociological motives. Violence against women, especially war rape, has been documented in many armed conflicts including those in Bosnia and Herzegovina, Cambodia, Haiti, Liberia and Uganda to ISIS crimes in Syria and Iraq. Furthermore, violence against women may occur in a variety of situations where girls and women are forced into prostitution, institutionalized sexual slavery, forced pregnancy and enforced sterilization, by an occupying power, it may also include gang rape which associated with specific battles or massacres. During war and armed conflict, rape is frequently used as a means of psychological warfare in order to humiliate the enemy. For this, rape can also be recognized as genocide and/or ethnic cleansing when committed with the intent to destroy, in whole or in part, a targeted group. We can say that systematic rape constitutes a grave breach of the Geneva Conventions and also constitutes a war crime in international and non-international armed conflicts respectively. However, the post-World War II Nuremberg trials condemned rape as a crime against humanity. There are other international legal instruments to prosecute perpetrators but this has occurred as late as the 1990s. Particularly, the International Criminal Tribunal for the former Yugoslavia and Rwanda have played a historic role in the prosecution of wartime sexual violence, which confirmed that “rape” constitutes a crime against humanity. Finally treaties and conventions have been put in practice, and violations punished, and also have paved the way for a more robust adjudication of such crimes worldwide. Governments must be willing to enforce international law and codes of conduct, while also supporting counseling and other services for victims.
Keywords: War rape; Armed conflict; sexual violence; military occupation